The Effect Of Competence, Job Stress And Perceived Organizational Support On Employee Performance With Organizational Commitments As Intervening Variables - Nolla Puspita Dewi; Intan Rahmadian; Jemmy Rumengan; Bambang Satriawan; Sri y; Nurhatisyah nurhatisyah; Ana Faizah (IAIC Publishing, 2021)
This study aims to analyze the effect of Competence, Job Sress, and Perceptual Organizational Support on Performance with Organizational Commitment as an Intervening Variable on Tanjungpinang City government employees. This type of research is associative causality. This research was conducted using a survey method by distributing questionnaires from government agencies in the Tanjungpinang City Government. The population of this study was all Regional Apparatus Organizations in Tanjungpinang City Government, totaling 31 Regional Apparatus Organizations, consisting of 97 sample respondents including the Head of Financial Subdivision, Head of Program Subdivision, Program Subdivision Secretary, Secretary, Development and Development Division of Control Programs in the Planning Agency, Development, Research and Development of Tanjungpinang City, and Inspectorate auditors. Data analysis methods used are descriptive statistical analysis and Partial Least Square (SEM-PLS) analysis. The results of this study indicate that competence has a significant effect on performance, work stress and perceived organizational support has no significant effect on performance. Competence does not significantly influence organizational commitment. Job stress and perceived organizational support have a significant effect on organizational commitment. Organizational commitment has no significant effect on performance. Indirectly, organizational commitment mediates the relationship of competence and organizational support, but does not mediate the relationship between work stress and performance